PKG-mediated MAPK signaling is necessary for long-term operant memory in Aplysia - Michel, Maximilian (Cold Spring Harbor Laboratory Press, 2011)
Signaling pathways necessary for memory formation, such as the mitogen-activated protein kinase (MAPK) pathway, appear highly conserved across species and paradigms. Learning that food is inedible (LFI) represents a robust form of associative, operant learning that induces short- (STM) and long-term memory (LTM) in Aplysia. We investigated the role of MAPK signaling in LFI memory in vivo. Inhibition of MAPK activation in animals prior to training blocked STM and LTM. Discontinuing MAPK signaling immediately after training inhibited LTM with no impact on STM. Therefore, MAPK signaling appears necessary early in memory formation for STM and LTM, with prolonged MAPK activity required for LTM. We found that LFI training significantly increased phospho-MAPK levels in the buccal ganglia. Increased MAPK activation was apparent immediately after training with greater than basal levels persisting for 2 h. We examined the mechanisms underlying training-induced MAPK activation and found that PKG activity was necessary for the prolonged phase of MAPK activation, but not for the early MAPK phase required for STM. Furthermore, we found that neither the immediate nor the prolonged phase of MAPK activation was dependent upon nitric oxide (NO) signaling, although expression of memory was dependent on NO as previously reported. These studies emphasize the role of MAPK and PKG in negatively reinforced operant memory and demonstrate a role for PKG-dependent MAPK signaling in invertebrate associative memory.